Rabies vaccination: Higher failure rates in imported dogs than in those vaccinated in Italy - Rota Nodari, E.; Alonso, Silvia; Mancin, M.; Nardi, M. de; Hudson-Cooke, S.; Veggiato, C.; Cattoli, G.; Benedictis, P. de (Wiley, 2017)
The current European Union (EU) legislation decrees that pets entering the EU from a rabies-infected third country have to obtain a satisfactory virus-neutralizing antibody level, while those moving within the EU require only rabies vaccination as the risk of moving a rabid pet within the EU is considered negligible. A number of factors driving individual variations in dog vaccine response have been previously reported, including a high rate of vaccine failure in puppies, especially those subject to commercial transport. A total of 21 001 observations collected from dogs (2006–2012) vaccinated in compliance with the current EU regulations were statistically analysed to assess the effect of different risk factors related to rabies vaccine efficacy. Within this framework, we were able to compare the vaccination failure rate in a group of dogs entering the Italian border from EU and non-EU countries to those vaccinated in Italy prior to international travel. Our analysis identified that cross-breeds and two breed categories showed high vaccine success rates, while Beagles and Boxers were the least likely to show a successful response to vaccination (88.82% and 90.32%, respectively). Our analysis revealed diverse performances among the commercially available vaccines, in terms of serological peak windows, and marked differences according to geographical area. Of note, we found a higher vaccine failure rate in imported dogs (13.15%) than in those vaccinated in Italy (5.89%). Our findings suggest that the choice of vaccine may influence the likelihood of an animal achieving a protective serological level and that time from vaccination to sampling should be considered when interpreting serological results. A higher vaccine failure in imported compared to Italian dogs highlights the key role that border controls still have in assessing the full compliance of pet movements with EU legislation to minimize the risk of rabies being reintroduced into a disease-free area.